Historical Narratives on Reconstruction of al-Aqsa Mosque in Early Islam: المسجد الأقصى بعد الاسلام - Al-Tel, Othman Ismael (Journal of Al-Tamaddun, 2021)
The aim of this paper is to examine historical accounts related the first demarcating re-construction of al-Aqsa mosque in Jerusalem after Islam. It focusing on the differences between the early and later sources by examining the early and later Islamic narratives and sources and the available non-Islamic sources. This research attempts to find some explanation behind the differences between the early and later sources. Through the analysis of the early sources, the author also discusses and analyses the views of some modern researchers who have dealt with some of these issues.